2016
DOI: 10.1186/s40104-016-0072-1
|View full text |Cite
|
Sign up to set email alerts
|

Superior growth performance in broiler chicks fed chelated compared to inorganic zinc in presence of elevated dietary copper

Abstract: BackgroundThe goal of this study was to compare the antagonism of elevated dietary Cu (250 mg/kg) from CuSO4 on three different Zn sources (ZnSO4 · H2O; [Zn bis(−2-hydroxy-4-(methylthio)butanoic acid)], Zn(HMTBa)2, a chelated Zn methionine hydroxy analogue; and Zn-Methionine), as measured using multiple indices of animal performance in ROSS 308 broilers.MethodsThree experiments were conducted in broiler chicks fed a semi-purified diet. All birds were fed a Zn-deficient diet (8.5 mg/kg diet) for 1 wk, and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 18 publications
2
10
0
1
Order By: Relevance
“…Better survivability in OTM fed groups indicates that birds belonging to inorganic group were less efficient to adopt with hot humid conditions. These findings agreed with the results of the recent studies [23,25,28].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Better survivability in OTM fed groups indicates that birds belonging to inorganic group were less efficient to adopt with hot humid conditions. These findings agreed with the results of the recent studies [23,25,28].…”
Section: Resultssupporting
confidence: 94%
“…Baloch et al [23] observed that OTM and ITM, when used in the diet, had no significant effect on FCR, which agreed with our result. Zhao et al [25] also showed that FCR was not affected by chelated Cu and three different sources of Zn as compared with inorganic zinc. Feed conversion, mortality, and tibia Zn were not affected by dietary treatments ( p > 0.5).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the underlying mechanism of action of oral zinc remains unknown [6]. Several theories of the mechanisms of action of zinc in the prevention and treatment of childhood diarrhea exist, including a mucosal-protective role, a diarrhea-induced zinc deficiency, an essential element in cell-mediated immunity, and a modifier of intra-luminal electrolyte secretion and absorption [6,[37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…The inorganic and organic forms of minerals affected growth performance, carcass characteristics, bone quality, and chemical composition of poultry birds. Chelated forms of minerals are also being used for better results (Zhao et al 2016). Increased levels of minerals like zinc along with phytase in diets of poultry lead to better utilization of nutrients and enhance production performances (Akter et al 2017).…”
Section: Advances In Delivery Of Nutraceuticalsmentioning
confidence: 99%